To study the serum C-reactive protein level and its correlation with prognostic variables in stable COPD patients - Srivastava, Nishant; Dave, Lokendra; Chaturvedi, Shivani; Dube, T N; Garde, Swapnil; Raghuvanshi, Mahendra (International Journal of Medical Research and Review, 2015)
Introduction: C-reactive protein is a stable and excellent biomarker of systemic inflammation which is easy to measure. COPD is an inflammatory disorder of lung with widespread Systemic manifestations and associated Systemic inflammatory response. C-reactive protein levels are increased in COPD patients. Present study investigated C-reactive protein level in stable COPD patients and its relation with clinically important outcome variable, exercise capacity. Method: Study included 56 stable COPD patients with mild to moderate severity in age group 40-70 years and 56 nonsmoking controls in the same age group. Clinical and physiological characteristics were determined and C-reactive protein levels were measured. Result: This study confirms the finding of higher C-reactive protein levels in smoker COPD patients (4.9 vs 4.0 mg-L-1) as compared to nonsmoker COPD patients. It also confirms that level of C-reactive protein in ex-smoker COPD population remains significantly higher than nonsmoker control group (4.9±0.5 vs 3.1mg/l). Conclusion: C-reactive protein level was strongly associated and correlated with 6 minute walk distance, FEV1 and GOLD stages, so C-reactive protein level can indirectly reflect prognosis of COPD patient and his exercise capacity. We recommend that measurement of C-reactive protein levels may be a useful tool to predict the prognosis and patient outcome in COPD patients. It also provides strong argument to develop therapies aimed at decreasing inflammation independent of smoking cessation.